Comparative high‐throughput analysis of sperm membrane proteins from crossbred bulls with contrasting fertility. (28th April 2022) - Saraf, Kaustubh Kishor; Kumaresan, Arumugam; Arathi, Bangalore Prabhashankar; Sundaresan, Nagalingam Ravi; Datta, Tirtha Kumar
Abstract: The aim of the present study was to identify fertility associated sperm membrane proteins in crossbred bulls. Sperm membrane proteins from high‐ and low‐fertile Holstein Friesian crossbred bulls ( n = 3 each) were subjected to high‐throughput liquid chromatography–mass spectrometry (LC–MS/MS) for comparative proteomic analysis. Proteomic profiling identified a total of 456 proteins in crossbred bull spermatozoa; it was found that 108 proteins were up regulated while 26 proteins were down regulated (>1.5‐folds) in spermatozoa from low‐ compared to high‐fertile bulls. Gene ontology classification revealed that upregulated proteins in low‐fertile bulls were involved in biological process such as oxidation–reduction process ( p = 3.14E−06), fusion of sperm to egg plasma membrane ( p = 7.51E−04), sperm motility ( p = 0.03), and capacitation ( p = 0.09), while down regulated proteins were associated with transport ( p = 6.94E−04), superoxide metabolic process ( p = 0.02), and tricarboxylic acid cycle ( p = 0.04). KEGG pathway analysis revealed that oxidative phosphorylation and tricarboxylic acid cycle pathways are the most significantly affected pathway in low‐fertile bulls. It was concluded that expression of proteins associated with oxidative phosphorylation and tricarboxylic acid cycle pathways were altered in low‐fertile crossbred bulls, and expression levels of SPATA19, ELSPBP1, ACRBP, CLU, SUCLA2, and SPATC1 could aid in assessing potential fertility of crossbred bulls.